The Legal Organization of the Right of Specialization and the Necessity of Adopting it in the Iraqi Civil Law (a Comparative Study) - Issa, Sidqi Muhammad Amin; Suleiman, Talib Ibrahim; Hussein, Faiq Muhammad (Journal of Legal and Political Studies, 2017)
There is no doubt that the subject of any right in general was taken into account and a wide Agreement and disagreement between legislators and jurists in the past and in recent times. The subject of our study (the right of specialization) is in this context. Some legislators have taken it as an in-kind subordination right, ,Including the Iraqi legislator, despite the importance of the rights in-kind subordination so that one of the creditors is assigned to real estate or property debt based on the issuance of a judgment enforceable obliging the debtor to debt, and this right differs from the rest of the rights in-kind dependency that was not present at the conclusion of the contract . Which is the result of the debt, as in the case of insurance and possessory property, exists at the time of the entry into force of the contract. The creditor shall, pursuant to this enforceable judgment, collect all of its debts from the real estate or property allocated to it.
Keywords: rightin kind; legislator; creditors; property